Aplikasi Monitoring Penggantian Kwh Meter Di Bidang BCP PT. PLN Selat Panjang - Adhamdi Tria Putra Abza (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
PT. PLN (Persero) Rayon Selatpanjang is a PLTD unit of a state-owned electricity company that was built to meet electricity needs in the Selatpanjang area. The system that is running in the monitoring section when inputting customer status requires the operator to retype the status of the customer who is replacing the KWH meter. In this study the author provides a solution in the form of a monitoring application for KWH meter replacement which is designed to manage customer status data using the Delphi 7.0 and SQL Server 2005 programming languages, then by using the monitoring application for KWH meter replacement, managing customer status data in the BCP field at PT. PLN (Persero) Rayon Selatpanjang will be safer and faster.